Effect of Sago Palm (Metroxylon sagu Rottb.) Maturity on Sucker Food Reserve and Survivability during Nursery Stage - STANLEY HOWELL, PETER; BULAN, PETRUS; PSYQUAY ABDULLAH, NUR ASHIKIN; BUSRI, NORAINI; JIWAN, MAKE (Borneo Journal of Resource Science and Technology, 2017)
Sago palm (Metroxylon sagu Rottb.) which accumulates starch in its trunk can be propagated through suckers which are normally nursed for at least six months before planting them to the field. Using suckers had been long practiced by local sago farmers as it is the most reliable source of planting materials for sago cultivation. However, effective and efficient sago suckers selection and extraction methodology had yet to been documented. The objective of the study was to determine the effect of sago palm maturity that influences the sucker food reserve availability and survivability during nursery stage. Sucker survivability was recorded from the observation and monitoring on nursed suckers using polyethylene nursery bag for six months. Chemical analysis on the sucker’s rhizome for sugar and starch content were determined using Anthrone and Somogyi-Nelson method, respectively. The result showed that sucker derived from mature mother palm have higher survival rate of 82.5 % than those from young mother palm with only 45% during nursery stage. Chemical analysis on the rhizome for sucker from mature mother palm showed higher percentage of starch and sugar with 29.21% and 4.38%, respectively as compared to suckers from young mother palm with only 9.37% starch and 3.92% sugar. The result showed that sago suckers derived from mature mother palm have higher food reserve stored in their rhizome for roots and leaves development which was critical for their survivability. This outcome strongly suggested that only sago suckers from mature mother palm are suitable to be selected as planting material than those from young mother palm. Keywords: Food reserve, nursery stage, palm maturity, sucker survivability